Sorghum pathology and biotechnology - a fungal disease perspective: Part II. Anthracnose, stalk rot, and downy mildew - Tesso, Tesfaye T.; Perumal, Ramasamy; Little, Christopher R.; Adeyanju, Adedayo; Radwan, Ghada L.; Prom, Louis K.; Magill, Clint W. (My University, 2012)
Foliar diseases and stalk rots are among the most damaging diseases of sorghum in terms of lost production potential, thus commanding considerable research time and expenditure. This review will focus on anthracnose, a fungal disease that causes both foliar symptoms and stalk rots along with the stalk rots caused by Fusarium spp. and Macrophomina phaseolina. Although the downy mildews are caused by oomycetes rather than true fungi, recent outbreaks have revealed resistance to previously effective chemical seed treatments and the evolution of new pathogenic races, once again pointing out the need for continuous vigilance. Sorghum diseases are described with respect to the causal organism or organisms, infection process, global distribution, pathogen variability and effects on grain production. In addition, screening methods for identifying resistant cultivars and the genetic basis for host resistance including molecular tags for resistance genes are described where possible along with prospects for future advances in more stable disease control.
Citation: Tesso, T., Perumal, R., Little, C., . . . Magill, C. (2011). Sorghum pathology and biotechnology - a fungal disease perspective: Part II. Anthracnose, stalk rot, and downy mildew. European Journal of Plant Science and Biotechnology, 6, 31-34.
Keywords: Colletotrichum sublinoleum; Colletotrichum graminicola; Fusarium; Macrophomina phaseolina; Peronosclerospora sorghi